Workforce Development Program untuk Pengembangan Masyarakat di Wilayah Operasi PT Chevron Pacific Indonesia - Meliza Putriyanti Zifi; Hamid Azwar; Retno Tri Wahyuni; Muhammad Ihsan Zul (Universitas Putra Indonesia YPTK Padang, 2022)
Workforce Development Program (WFD) is a community service program implemented by Politeknik Caltex Riau funded through a cost recovery mechanism by SKK Migas and PT. Chevron Pacific Indonesia (CPI). The background of this program relates to the unemployment rate condition in Riau Province (6.32%). This fact aggravated when Covid-19 hits the world and has an impact on laborers/workers lives, especially in Riau. There are workers who got termination as employment, some of them being laid off directly. WFD aims to provide additional skills and certificates for the workforce in Riau to have higher competitiveness index. The WFD program is implemented through the training and certification activities in the fields of Occupational Safety, Health and Safety Experts (AK3), Oil and Gas Occupational Safety, Health and Safety Operators, and Dump Truck Operators. The stages of the implementation program include socialization, recruitment, opening program, training, and certification (online, offline and blended training), and closing. There are 103 participants who pass as WFD 2021 beneficiaries. There are 101 participants who have passed the certification. The graduation achievement of the 2021 WFD Program is 98.06% (101/103). Based on the results of alumni tracing conducted 1 month after the training and certification phase, there were 25% of participants stated that the competencies they had when participating in WFD were able to increase their income.